The State of Virtualisation at a Selected University in the Eastern Cape Province of South Africa - Mefi, Nteboheng Patricia; Asoba, Samson Nambei (Journal of Ecohumanism, 2025)
Virtualisation in higher education emerged as a new imperative after the covid-19 pandemic as well as the technological revolution. Technological revolution and virtualisation have, however, put attention once more on socioeconomic inequalities in South Africa. Inequalities in readiness and adoption of digital systems have been observed along geographical as well as socioeconomic dimensions in resulting in a need to inquire on the state of virtualisation in different contexts. The study sought to describe the state of virtualisation at a selected university in the Eastern Cape Province which is considered one of the poorest in South Africa. Specifically, the state of virtualisation was described in terms of three dimensions, namely; (1) perception of academics on virtualisation, (1) attitudes of academics on virtualisation and (2) university initiatives in promoting virtualisation. The study adopted a qualitative design based on interviews with nine (9) academics from a selected university in the Eastern Cape. The perceptions of virtualisation were found to be consistent with those of the literature where virtualisation was considered to imply remote teaching and learning, digitalisation as were as non-physical educational strategies. Virtualisation was found to be associated with both negative and positive attitudes. Positive attitudes were related to views that virtualisation was flexible, associated with learning everyone and increased access to education. Negative attitudes were found to stem from information overload as well as sentiments that virtualisation needed specialised resources and training. It was found that University has done considerably better in training academics as well as in providing them with relevant tools for virtualisation. The study recommends strengthening virtualisation to ensure every academic benefits from using it.